Simulation of Signalless Intersection Handling Using the VISSIM Model at the Punge Intersection, Banda Aceh City, Indonesia - M. Isya; Yusria Darma; Rachmat Taufiqy; Juliana Fisaini; M. Faisi Ikhwali; Wisnu Prayogo; I Wayan Koko Suryawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
The Punge Intersection is one of the four-armed unsignalized intersections in Banda Aceh City without traffic regulations such as traffic lights, roundabouts, or other warning signs. This condition is very troublesome for road users, especially during peak hours. It is considered necessary to evaluate the performance of the intersection along with alternative treatments that produce the best performance to meet the standards. Most of the previous studies relied heavily on tailor-made simulation tools to evaluate control algorithms, but the use of simulation platforms to make system comparisons through modeling is still very rare, especially in Indonesia. Analysis and modeling at the Punge Intersection using the MKJI method and PTV VISSIM 10.00-02 (VISSIM) software. Traffic volume data (plan), road geometric, and environmental conditions are needed in data processing operations using VISSIM. Three modeling scenarios were carried out with the implementation of a one-way road for arm A in the entry direction, installation of a traffic signaling tool, called APILL, roundabout planning and widening of each arm. A roundabout planning simulation with type R10-22 with widening on each road section can make the Punge Intersection with the best LOS and meet the best service levels.